Measuring objective physical activity in people with chronic low back pain using accelerometers: a scoping review - Mathilde Berger; Mathilde Berger; Anne Martine Bertrand; Thomas Robert; Laurence Chèze (Frontiers in Sports and Active Living, 2023)
PurposeAccelerometers can be used to objectively measure physical activity. They could be offered to people with chronic low back pain (CLBP) who are encouraged to maintain an active lifestyle. The aim of this study was to examine the use of accelerometers in studies of people with CLBP and to synthesize the main results regarding the measurement of objective physical activity.MethodsA scoping review was conducted following Arksey and O'Malley's framework. Relevant studies were collected from 4 electronic databases (PubMed, Embase, CINHAL, Web of Science) between January 2000 and July 2023. Two reviewers independently screened all studies and extracted data.Results40 publications out of 810 citations were included for analysis. The use of accelerometers in people with CLBP differed across studies; the duration of measurement, physical activity outcomes and models varied, and several limitations of accelerometry were reported. The main results of objective physical activity measures varied and were sometimes contradictory. Thus, they question the validity of measurement methods and provide the opportunity to discuss the objective physical activity of people with CLBP.ConclusionsAccelerometers have the potential to monitor physical performance in people with CLBP; however, important technical limitations must be overcome.